Web-Based Youth Forum Application (WBYFA) - Alksher, Mostafa Ahmed (2008)
Web-based forum is an application through the internet to facilitate the process of discussions and exchange of ideas. It is also referred to as online forums, message boards, discussion groups, and discussion forums. Youth can play a role in shaping their societies of immense diversity through the means of communication and participation, and sharing ideas. Therefore, this study leads to develop a web-based forum application to help young people express themselves and their needs, and desires. The requirements of the web-based application are identified from the students in UUM who are in the similar age group, design the application, and a prototype to implement the design.